The education process viewed from the standard-based education paradigm in public schools: a case from Central Java, Indonesia - Zamili, Moh. (Management and Entrepreneurship: Trends of Development, 2021)
The purpose of this study is to analyze the education process in Indonesia using a standard-based education paradigm in the process aspect. The study focused on public high school students on four educational standards released by the Central Java Provincial Education Quality Assurance Agency. Methodology: Case studies were selected based on data from national education standards. Data analysis processed using ATLAS.ti version 8. The research findings: the results showed the absence of regulations regarding improving teacher qualifications have worsened the standard achievement. Excessive implementation of educational concepts and ignorance of collaborative assessment of spiritual aspects obscures understanding of religious tolerance as a hallmark of Indonesian Education. JEL Classification: I2, I21, I28.